MRNA stability and control of cell proliferation. (21st September 2011) - Mazzoni, Cristina; Falcone, Claudio
Abstract : Most of the studies on cell proliferation examine the control of gene expression by specific transcription factors that act on transcriptional initiation. In the last few years, it became evident that mRNA stability/turnover provides an important mechanism for post-transcriptional control of gene expression. In eukaryotes, mRNAs are mainly degraded after deadenylation by decapping and exosome pathways. Mechanisms of mRNA surveillance comprise deadenylation-independent pathways such as NMD (nonsense-mediated decay), when mRNAs harbour a PTC (premature termination codon), NSD (non-stop decay, when mRNAs lack a termination codon, and NGD (no-go decay), when mRNA translation elongation stalls. Many proteins involved in these processes are conserved from bacteria to yeast and humans. Recent papers showed the involvement of proteins deputed to decapping in controlling cell proliferation, virus replication and cell death. In this paper, we will review the newest findings in this field.